Mental Illness Stigma Intervention in African Americans: Examining Two Delivery Methods. Issue 5 (May 2016) - Vinson, Ebony S.; Abdullah, Tahirah; Brown, Tamara L.
Abstract : Abstract: Stigma surrounding mental illness and mental health treatment remains a significant problem, particularly among African Americans. This study sought to examine the effects of 2 intervention delivery methods in reducing reported stigma. African Americans (n = 158) were nonrandomly assigned to an in-person contact or video condition and administered a survey immediately before, after, and 2 weeks following the stigma intervention. The in vivo contact condition consisted of an African American man discussing his experiences with mental illness and psychotherapy. The session was recorded, and the recording was used for the video condition. There were no significant effects based on delivery method; however, there was a significant effect for time on stigma and help-seeking attitude measures. Further research is needed to determine the overall effectiveness of the intervention.